Clinical Outcomes and Reduced Pulmonary Artery Pressure With Intra-Aortic Balloon Pump During Central Extracorporeal Life Support. Issue 2 (February 2019) - Tepper, Sarah; Garcia, Moises Baltazar; Fischer, Irene; Ahmed, Amena; Khan, Anam; Balsara, Keki R.; Masood, Muhammad Faraz; Itoh, Akinobu
Abstract : Abstract: Patients supported with extracorporeal life support (ECLS) can experience severe complications from increased left ventricular afterload. The intra-aortic balloon pump (IABP) is thought to unload the left ventricle (LV) and is routinely used with ECLS despite conflicting evidence of its clinical benefit. This retrospective, single-center study examined the effect of the simultaneous use of IABP and centrally cannulated ECLS on patient outcomes and provides new insights into IABP-mediated LV unloading. Thirty patients supported with central ECLS and IABP (extracorporeal life support-IABP group, ECLS-I) were compared with 30 patients with central ECLS alone (ECLS) for cardiogenic shock. Rates of survival to 30 days ( p = 0.06) and intensive care unit (ICU) discharge ( p = 0.17), and clinical outcomes were not significantly different between the two groups. In patients with pulmonary artery pressure monitoring, mean pulmonary artery (PA) pressure was significantly reduced after 24 ( p = 0.007) and 48 hours ( p = 0.002) in the ECLS-I group. No significant difference in PA pressure was observed in the ECLS group after 24 or 48 hours. The IABP has the ability to reduce pulmonary artery pressure in patients supported by central ECLS. However, this did not translate into improved survival or clinical outcomes in our population.